Incidence and presentation of new-onset type 1 diabetes in children and adolescents from Germany during the COVID-19 pandemic 2020 and 2021: current data from the DPV Registry - Bächle, Christina; Eckert, A.; Kamrath, C.; Neu, A.; Manuwald, Ulf; Thiele-Schmitz, S.; Weidler, O.; Knauer-Fischer, Sabine; Rosenbauer, J.; Holl, R. W. (Diabetes research and clinical practice, 2023)
Aims - To determine whether the incidence of type 1 diabetes mellitus (T1D), autoantibody-negative diabetes, and diabetic ketoacidosis (DKA) at diabetes onset in 2020 and 2021 changed when compared to long-standing trends. - Methods - Our study is based on diabetes manifestation data of the 0.5-<18-year-old children/adolescents from the German multicenter Diabetes Prospective Follow-up Registry. Based on long-term pre-pandemic trends from 2011 to 2019, we estimated adjusted incidence rate ratios (IRR) for T1D and DKA, and prevalence rate ratios (PRR) regarding autoantibody status with 95 % confidence intervals (CI) for the years 2020 and 2021 (observed versus predicted rates), using multivariable negative binomial or beta-binomial regression, respectively. - Results - We analyzed data of 30,840 children and adolescents with new-onset T1D. The observed incidences were significantly higher than the predicted incidences (IRR2020 1.13 [1.08-1.19]; IRR2021 1.20 [1.15-1.26]). The prevalence of autoantibody-negative diabetes did not change (PRR2020 0.91 [0.75-1.10]; PRR2021 1.03 [0.86-1.24]). The incidence of DKA during the pandemic was higher than predicted (IRR2020 1.34 [1.23-1.46]; IRR2021 1.37 [1.26-1.49]). - Conclusions - An increase in the incidences of T1D and DKA, but not of autoantibody-negative diabetes was observed during both pandemic years. Further monitoring and efforts for DKA prevention at onset are necessary.
Online verfügbar: 8. Februar 2023, Artikelversion: 19. Februar 2023
Gesehen am 21.05.2024